Brand Valuation with Hirose Method: An Application in Kazakhstan - Syzdykova, Aziza; Azretbergenova, Gulmira; Zhetibayev, Zhanture (International Review of Management and Marketing, 2025)
Although brand value measurement is essential, a common consensus has yet to be reached. In the literature, financial-based, consumer-based and mixed brand valuation methods are used together. While financial-based brand value is calculated according to the financial data of the companies, consumer-based brand value reveals the brand value according to the perceptions and preferences of the consumers. In the literature, it has been observed that the survey method is generally used in studies where brand value is determined based on consumer behaviour, and the most commonly used method in studies where brand value is determined based on financial foundations is the Hirose method. However, this study will be the first study conducted on companies in Kazakhstan using the Hirose method. In this study, the brand value of LOTTE Rakhat JSC (Rakhat) was calculated using the financial data of two companies traded on the KASE stock exchange of Kazakhstan and operating in the field of food, which can be associated with the brand. This study is the first to use the Hirose method to measure brand equity in Kazakhstan and will pave the way for future studies.